Improving Knowledge and Skills in Farming with Verticulture Hydroponics - Muchlisiniyati Safeyah; Susi Hardjati; Azkia Avenzoar; Muhammad Aris Ichwanto (Nusantara Science and Technology Proceedings, 2022)
Farming with verticulture hydroponics is a trend in urban areas. Verticulture hydroponics can overcome land limitations, is easy to implement, and can take advantage of used goods. Kampung Kapas Lor Kulon Surabaya is a densely populated village and buildings, minimally greened, and seems shabby. The purpose of community service carried out is to improve the knowledge and skills of verticulture hydroponic farming in Dasa Wisma RT 04 Kapas Lor Kulon Surabaya. The methods used are observation, analysis of potentials and problems, implementation through counseling and training, and evaluation. Evaluation is carried out through questionnaires before and after training, as well as monitoring in the field. The hydroponic system used is an axis system, and a DFT (Deep Flow Technique) system. The results of the evaluation showed that there was an increase in knowledge and skills in the trainees. Knowledge of the notion of verticulture hydroponics increased quite sharply from 21.25% to 95%. Hydroponic farming skills have also improved, ranging from seed seeding, and plant removal, to plant care. The mothers' awareness of using second-hand goods to grow crops is also very good.